TEMPERATURE FREQUENCY CHARACTERISTICS OF CHARGE TRANSITION IN THE Li0.5Fe2.4Ti0.1O4 NON-STOICHIOMETRIC SYSTEM - I.M. Gasyuk; V.V. Ugorchuk; L.S. Kaykan; B.J. Deputat (Vasyl Stefanyk Precarpathian National University, 2014)
A study of conductivity temperature frequency dependence of Li0.5Fe2.4Ti0.1O4 non-stoichiometric spinel has exhibited frequency dispersion conductivity presence. The time of relaxation (τ) proved to make 2·10-6s within the limits of dispersion. The conductivity size was found to be dependant upon the amount of Fe2+ ions in the structure.